2014
DOI: 10.1093/logcom/exu067
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic semantics for a modal logic close to S1

Abstract: The modal systems S1-S3 were introduced by C. I. Lewis as logics for strict implication. While there are Kripke semantics for S2 and S3, there is no known natural semantics for S1. We extend S1 by a Substitution Principle SP which generalizes a reference rule of S1. In system S1+SP, the relation of strict equivalence ϕ ≡ ψ satisfies the identity axioms of R. Suszko's non-Fregean logic adapted to the language of modal logic (we call these axioms the axioms of propositional identity). This enables us to develop … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(50 citation statements)
references
References 18 publications
2
48
0
Order By: Relevance
“…One immediately recognizes that all Lewis systems S1-S5 satisfy the axioms (Id1) and (Id2) of propositional identity if ϕ ≡ ψ is defined as strict equivalence (ϕ → ψ) ∧ (ψ → ϕ). 2 In [5,6] we proved that S3 is the weakest Lewis modal logic where strict equivalence satisfies all axioms of propositional identity (Id1)-(Id3). Moreover, in [5] we showed that logic S1+SP, i.e.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…One immediately recognizes that all Lewis systems S1-S5 satisfy the axioms (Id1) and (Id2) of propositional identity if ϕ ≡ ψ is defined as strict equivalence (ϕ → ψ) ∧ (ψ → ϕ). 2 In [5,6] we proved that S3 is the weakest Lewis modal logic where strict equivalence satisfies all axioms of propositional identity (Id1)-(Id3). Moreover, in [5] we showed that logic S1+SP, i.e.…”
Section: Introductionmentioning
confidence: 92%
“…System S1+ SP then results from S1 by adding all instances of SP as theorems. We saw in [5] that S1+SP S1+ SP ⊆ S3. In particular, all instances of SP are derivable in S3, and S3 is the weakest among Lewis' modal logics with that property.…”
Section: Deductive Systemsmentioning
confidence: 98%
See 3 more Smart Citations